Thermal Analysis of Creep Feed Grinding. (2015) - Ortega, N.; Bravo, H.; Pombo, I.; Sánchez, J.A.; Vidal, G.
Abstract: Creep feed grinding is an abrasive finishing process characterized by low feed speeds (0.05-0.5 m/min) and very high depths of cut (0.1-30 mm). Thanks to the extraordinary material removal rate provided together with a high shape accuracy obtained over complex profiles, this process has become the main competitor of milling. However, creep feed grinding has also some limitations that should be overcome. The major limitation is the thermal damage on the machined part and the rapid wheel wear. Since heat distribution depends strongly on the workpiece geometry, a 3D FEM thermal model has been programmed for the generation of a square in order to study the effect of the side wall height on the heat distribution on both, the wall and the ground part. Thermal model has been validated by means of experimental tests being the heat ratio to the workpiece the adjusting parameter. General results show that the higher the side wall, the higher the temperatures. Friction between the wheel and the side wall contributes to higher power consumption.